Case report: Moderate therapeutic response to Bevacizumab in late-onset Labrune syndrome - Wang, Meiping; Lu, Jinmei; Wang, Xiaoxi; Ba, Xiaoqun; Wu, Dengchang; Zhang, Jianfang; Zhou, Jiajia; Wang, Kang (Frontiers in Neurology, 2022)
Labrune syndrome (LS) is caused by SNORD118 gene mutations with a particular neuroimaging of white matter disease, intracranial calcification and cysts. There was no effective 20 treatment until now. An 18-year-old male with infancy-onset LS was first treated with vascular endothelial growth factor (VEGF) inhibitor Bevacizumab for one year, resulting in significant clinical and radiological improvements. We adopted similar regimen in a late-onset LS patient and, demonstrated moderate cognitive improvements but without changes on imaging. As such, Bevacizumab could potentially be clinically effective in adult-onset LS with great 25 safety.